Economic impacts of petroleum industry in states of Pahang and Terengganu - Mohd Yusof Saari,; Muzafar Shah Habibullah,; Chakrin Utit,; Maji, Ibrahim Kabiru (Penerbit Universiti Kebangsaan Malaysia, 2018)
Petroleum industry in Malaysia has created significant contribution to the Malaysian economy as a whole. However, the growth and development of the industry does not necessarily to bring considerable economic linkages to the local and neighboring economies where the industry is located, and thus fail to contribute to the economic diversification of local economies. This paper validates this expectation by examining the economic impacts of petroleum industry in the states of Terengganu and Pahang. Regional input-output model that developed by using location quotient, has been used as the main methodology in this paper. Results are consistent with our expectation that the state of Terengganu does not benefit largely from the petroleum industry but contributes more to the economic diversification for the state of Pahang. One of the explanations to this finding is that petroleum related activities such as petroleum refinery and support services are outsourced to the state of Pahang.